Penerapan Metode Token-Based sebagai Mekanisme Autentikasi pada IoT Middleware - Aditya Chamim Pratama; Eko Sakti Pramukantoro; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The existing IoT middleware has been developed to answer the challenge of syntactical interoperability by creating a gateway so that it can communicate through the CoAP, MQTT and WebSocket protocols. However, the middleware can accept data from anywhere and various nodes that are not entitled to connect to the middleware. So we need an additional mechanism on the IoT middleware to authenticate the node that will communicate. Authentication is a guarantee that all involved in system communication are valid entities. Therefore, in this research, the development of IoT middleware is done by adding the JSON Web Token (JWT) authentication mechanism. JWT is a token that represents a concise message called claims and is protected by a digital signature, in addition, JWT tokens have an expiration time. JWT tokens are used because of their compact size so they can be sent via URL, query or header. Based on the test results, the authentication mechanism that is applied is able to authenticate the token sent by the node. The impact of applying the authentication mechanism to the IoT middleware causes the node to increase the time it takes to establish connections and publish or subscribe. Compared to IoT middleware without authentication, the average time difference generated is below 30 milliseconds.